Alcobaça: routing ceramics - Rodrigues, Diana (2012)
The current project aims to know the idiosyncrasies of ornamental ceramics sub-sector, from Alcobaça (Portugal). Later, it will be suggested a set of actions to improve it, trying to refrain its negative trend. This paper applies the idea of cluster, from Michael Porter, to the analyzed factories showing how they compete and cooperate at the same time. Consequently, it extends the referred concept to the possibility of an inter-firm umbrella brand, where all those enterprises can join efforts under a common strategy. This is particularly relevant, once many of them lack marketing pro-activity. Thus, based in the differential advantages of this industrial agglomeration, it will be presented several actions to make it more competitive and attractive to investment.